Pedagogical Documentation as a “Bridge” Between Parents and the Early Childhood Curriculum - Domna (Mika) Kakana; Alexandra Gkloumpou (Social Sciences)
Parents’ involvement in early childhood education is of great importance. In Greece, many educators still hesitate to involve parents in their school’s daily program. They also do not use pedagogical documentation in the educational process as it is not included in the official curriculum. Our main goal was to bring parents closer to the early childhood curriculum, in an active and participatory way, through the documentation process. The main research question referred to the way in which the systematic use of pedagogical documentation can help parents understand the kindergarten’s daily curriculum and participate in it in a new way, in a country where pedagogical documentation is not mandatory. We used collaborative action research between ten kindergarten educators from five schools and two researchers from the same university department. The methodological tools were a researchers’ diary, two digital questionnaires for the educators (pre-/post-implementation) and a post-implementation digital questionnaire for the parents. The results showed that the documentation helped the educators to bring the parents closer to the kindergarten’s daily program and made them feel as if they could participate in it creatively. Also, the documentation derived from the children, educators and parents constructed a community of relations, participation, shared values and learning among them.